Integrated Management of Arthropod Pests and Insect Borne Diseases 2010
DOI: 10.1007/978-90-481-8606-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic Nematode Ecology and Biological Control in Florida Citrus Orchards

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…An ongoing survey of EPN spatial patterns in Florida using qPCR for detection and quantification revealed that Hi was the most frequently encountered and often the dominant species in most soil types (Campos-Herrera et al, 2010). The inferior persistence of Hi in the present experiments illustrates the difficulty of approximating field conditions in controlled experiments.…”
Section: Discussionmentioning
confidence: 92%
“…An ongoing survey of EPN spatial patterns in Florida using qPCR for detection and quantification revealed that Hi was the most frequently encountered and often the dominant species in most soil types (Campos-Herrera et al, 2010). The inferior persistence of Hi in the present experiments illustrates the difficulty of approximating field conditions in controlled experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent field studies routinely detected S. diaprepesi, Steinernema sp. glaseri-group, S. riobrave, H. indica and H. zealandica (Campos-Herrera et al, 2010;Duncan et al, 1996Duncan et al, , 2003aDuncan et al, , 2007. The detection of S. scapterisci here is a new record that expands the known EPN diversity in Florida citrus groves.…”
Section: Speciesmentioning
confidence: 97%
“…Because real time qPCR and DNA barcoding using NGS are currently the most widely used methods for the study of belowground interactions in agroecosystems, important differences in the requirements for both methods are summarized in Table 2. Technical aspects about the development of these protocols were extensively detailed in Bustin et al (2009); Campos-Herrera et al (2010); van Pelt-Verkuil et al (2010) and Pompanon et al (2012). The first step is selecting the most appropriate method to address the question.…”
Section: Molecular Techniques For Characterizing Soil Communities Andmentioning
confidence: 99%